MENELUSURI MAKNA PERCERAIAN DALAM HUKUM ISLAM: PERBANDINGAN DALAM FIQH KONVENSIONAL DAN UU KONTEMPORER DI INDONESIA DAN NEGARA-NEGARA MUSLIM, PERSPEKTIF HAM DAN CEDAW - Nuning Rodiyah (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2018)
This research is aimed to measure how far a marriage divorce in conventional fiqh that mostly places women in a weaker position towards men’s action. Anytime the men could make a divorce, though the women do not want it being happened. In any condition, when the men said the word “talak”, so be it, even when the men in drunken or humorous condition. This concept is so discriminative against the women, so the correction is needed. This article focuses in talking about the problems inside the family, especially related to the divorce in classical fiqh. This discourse will see how far its relevancy to be implemented in Indonesia, using the perspective of Human Rights, CEDAW, Anti-Discrimination Laws, and how the government take intervene on this problem.